2013
DOI: 10.1002/pro.2332
|View full text |Cite
|
Sign up to set email alerts
|

Substrate‐dependent dynamics of UDP‐galactopyranose mutase: Implications for drug design

Abstract: Trypanosoma cruzi is the causative agent of Chagas disease, a neglected tropical disease that represents one of the major health challenges of the Latin American countries. Successful efforts were made during the last few decades to control the transmission of this disease, but there is still no treatment for the 10 million adults in the chronic phase of the disease. In T. cruzi, as well as in other pathogens, the flavoenzyme UDP-galactopyranose mutase (UGM) catalyzes the conversion of UDP-galactopyranose to U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 38 publications
2
33
0
Order By: Relevance
“…MD simulations have also been used to study substrate-associated active site motion in TcUGM [58]. Classical and accelerated MD simulations agree with the proposed hypothesis that ligand binding influences the open-closed equilibrium of the mobile flaps.…”
Section: Molecular Dynamics Studies Of Active Site Flexibilitymentioning
confidence: 72%
See 1 more Smart Citation
“…MD simulations have also been used to study substrate-associated active site motion in TcUGM [58]. Classical and accelerated MD simulations agree with the proposed hypothesis that ligand binding influences the open-closed equilibrium of the mobile flaps.…”
Section: Molecular Dynamics Studies Of Active Site Flexibilitymentioning
confidence: 72%
“…Classical and accelerated MD simulations agree with the proposed hypothesis that ligand binding influences the open-closed equilibrium of the mobile flaps. After extensive MD simulations of both substrate-free and substrate-bound TcUGM, it was observed that both flaps open in the absence of ligand, thus creating a channel for ligand uptake [58]. When UDP-Gal p is bound, intramolecular interactions help maintain both flaps closed.…”
Section: Molecular Dynamics Studies Of Active Site Flexibilitymentioning
confidence: 99%
“…The aMD approach is especially attractive because it does not require a priori knowledge of the reaction path. This technique has been successfully used during the last years by our group to sample conformational changes occurring on the micro‐ to millisecond time scales …”
Section: Methodsmentioning
confidence: 99%
“…This technique has been successfully used during the last years by our group to sample conformational changes occurring on the micro-to millisecond time scales. [28][29][30][31] The implementation of aMD allows modification of both the total potential energy (V total ) of the system as well as the dihedral potential energy (V dihed ). It is possible to modify only the first one, only the second one or both of them at the same time; that is, the dihedral energy is doubly modified or more accelerated than other terms.…”
Section: Accelerated MDmentioning
confidence: 99%
“…The presence of a covalent flavin-N5-adduct was demonstrated in eUGMs [41] and the structures of the free enzyme and in complex with UDP-Gal p in the oxidized and reduced state have been elucidated [4245]. These structures revealed conformation changes in the active site flaps, which open in the absence and close in the presence of substrate.…”
Section: Priming the Flavin-n5 For Reactivity In Non-redox Reactionsmentioning
confidence: 99%